EPHTAH!: das ideias pedagógicas de Murray Schafer - Abreu, Thiago Xavier de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aims to discuss the pedagogical ideas of Murray Schafer. “Pedagogical ideas” are here understood as the educational philosophy that guides and composes the practice of teaching. Through the bibliographic review of Schafer‟s work, alongside specialized periodicals and related literature, three central axes that comprise his pedagogical ideas are proposed: ecology, spiritual experience and the aesthetical experience. Each of these axes was considered as a result of a historical development that generates philosophical conceptions from a process of contradictions between ideas. Thus, we discuss the ecology and spiritual experience through the dichotomy between mechanistic thinking and ecological thinking, i.e. the connection/separation relationship between man and the whole. The aesthetic experience was considered by the educational perspective, and analyzed by the dichotomy between the pedagogical currents that are based on an ideal of man to build educational proposals (pedagogies of essence) and currents which take man as he really is (pedagogies of existence). This analysis was correlated with the work of Murray Schafer, inserting the author in the context of these dichotomies. With this, we can observe the construction of his worldview, as well as the structure, objectives and considerations which underlie his pedagogical practice. His pedagogical ideas show a pattern of interaction between the axes discussed: the sacralization of the aesthetic experience of soundscape as a mediator of the ecological relation between the individual and the whole, i.e. a spiritual relationship between art and the individual as a means of connection from the singular to the total, understood here from an ecological perspective. This study intends to assist the pedagogical activity of teachers that employ the educational conceptions of Murray Schafer in the teaching of music, hoping that by providing ...

O presente trabalho tem por objetivo discutir as ideias pedagógicas de Murray Schafer. Consideramos “ideias pedagógicas” a filosofia educacional que orienta e que é substância da atividade prática de ensino. Por meio de revisão bibliográfica de obras de Schafer, de periódicos especializados e de literatura relacionada a estas obras, formatamos três eixos centrais que permeiam suas ideias pedagógicas: a ecologia, a experiência espiritual e a experiência estética. Cada um deles foi considerado como consequência de um desdobramento histórico, o qual gera concepções filosóficas a partir de um processo de contradição entre ideias. Sendo assim, discutimos a ecologia e a experiência espiritual por meio da dicotomia entre o pensamento mecanicista e o pensamento ecológico, isto é, a relação ligação/separação entre o homem e a totalidade. A experiência estética foi considerada pelo prisma educacional, e analisada pela dicotomia entre as correntes pedagógicas que partem de um ideal de homem para erigir propostas educacionais (pedagogias da essência) e as que tomam o homem como ele realmente é (pedagogias da existência). Toda esta análise foi relacionada à obra de Murray Schafer, inserindo-o no contexto das referidas dicotomias. Isso nos mostra, tanto a construção de sua visão de mundo, quanto a estrutura, os objetivos e as reflexões que subjazem a sua prática educacional. Suas ideias pedagógicas apontam para um padrão de interação entre os eixos discutidos: a sacralização da experiência estética da paisagem sonora como mediadora da relação ecológica entre o indivíduo e o todo, ou seja, uma relação espiritual entre a arte e o indivíduo como meio de conexão entre ele e a totalidade, entendida aqui da perspectiva ecológica. Pretendemos que este trabalho auxilie na atividade pedagógica de professores que tomam as concepções educacionais de Murray Schafer ...
Keywords: Schafer, R. Murray (Raymond Murray), 1933-; Musica - Filosofia e estetica; Musica - Instrução e estudo; Ecologia humana; Music - Instruction and study